2021
DOI: 10.1111/1365-2435.13874
|View full text |Cite
|
Sign up to set email alerts
|

Predator abundance drives the association between exploratory personality and foraging habitat risk in a wild marine meso‐predator

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…The relative trophic simplicity of a high-latitude shallow lake with clearly distinct trophic niches may facilitate the detection of the currently observed correlation between behavior and δ 13 C values. This is likely to vary system to system, for example, Dhellemmes et al (2021) observed correlation between behavior and distinct δ 13 C niches of different foraging risk (seagrass and mangroves) but as the trophic environment increases in complexity small-scale differences in foraging may be less likely to result in notable differences in stable isotope values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative trophic simplicity of a high-latitude shallow lake with clearly distinct trophic niches may facilitate the detection of the currently observed correlation between behavior and δ 13 C values. This is likely to vary system to system, for example, Dhellemmes et al (2021) observed correlation between behavior and distinct δ 13 C niches of different foraging risk (seagrass and mangroves) but as the trophic environment increases in complexity small-scale differences in foraging may be less likely to result in notable differences in stable isotope values.…”
Section: Discussionmentioning
confidence: 99%
“…Following Glon et al (2016), there have only been a few studies combining measures of personality and stable isotope estimates of trophic niche. Dhellemmes et al (2021) found that exploratory behavior in juvenile lemon sharks (measured in a controlled test) correlates with δ 13 C values representing sheltered or unsheltered foraging habitats but only when predators were abundant. A recent study on red knots found that observations of both foraging behavior in the field and stable isotope values were related to personality (exploratory behavior) suggesting an effect of personality on tropic niche (Ersoy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a marine coastal system, Dhellemmes et al. (2021) found that the relationship between individual juvenile lemonshark ( Negaprion brevirostris ) exploration and isotopic signatures of foraging in high‐risk, exposed eel grass habitats fluctuated in direction and magnitude according to predation pressure. Gharnit et al.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Euricea nana salamanders reduce their activity time in the presence of predators ( Davis & Gabor, 2015 ). Likewise, Parus major tits exposed to predators have a lower tendency to explore than non-exposed controls ( Abbey-Lee, Mathot & Dingemanse, 2016 ), and juvenile Negaprion brevirostris sharks that exhibit more exploratory behaviour forage in riskier habitats, but only under low predation pressure ( Dhellemmes et al, 2021 ). On the other hand, the relationships between predation risk and behavioural traits may transcend plasticity, as behaviour can be persistent across environments ( Dosmann & Mateo, 2014 ).…”
Section: Introductionmentioning
confidence: 99%